KONSELING ISLAM MULTIKULTURAL PADA MASYARAKAT BANJAR DAN BUGIS KABUPATEN KOTABARU KALIMANTAN SELATAN - Apriani, Siti Sarah (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2024)
The purpose of this study is to provide advice in preventing inter-ethnic conflict in Kotabaru District. The subject in this study is multicultural Islamic counseling as an option or suggestion to prevent or overcome problems in the Kotabaru community group, while the object of this research is the Banjar and Bugis communities, because these two tribes have a large population in the Kotabaru area, to be precise in Pulau Laut District. North. This study used a qualitative research method with a literature study approach. The results of this study indicate that the majority of Kotabaru people are Muslim with various ethnicities and cultures, so to provide appropriate counseling services is to provide Islamic counseling with a multicultural approach so that clients can accept differences in a society and help counselees to realize their imperfections as human beings. A good counseling process certainly cannot be separated from the role of the counselor who in this case is required to have Islamic insight and understand and be sensitive to the characteristics and culture of the Banjar and Bugis communities.